Multimodality imaging in Fabry cardiomyopathy: from early diagnosis to therapeutic targets. (20th September 2018) - Militaru, Sebastian; Ginghină, Carmen; Popescu, Bogdan A; Săftoiu, Adrian; Linhart, Ales; Jurcuţ, Ruxandra
Abstract: Fabry disease (FD) is a rare genetic X-linked disorder that can impact multiple organs. Cardiac involvement influences the prognosis of patients with FD, being one of the main causes of mortality. Cardiac imaging has proven essential in all aspects of Fabry cardiomyopathy evaluation, such as diagnosis (including detection of early organ changes), disease progression, and guideline for starting enzyme therapy. Imaging techniques used in cardiac evaluation of FD range from 2D and deformation studies in echocardiography to cardiac magnetic resonance (CMR), cardiac scintigraphy and positron emission tomography. The present review summarizes the imaging 'red flags' demonstrated to be able to differentiate early cardiac FD from normal controls and Fabry cardiomyopathy from other causes of hypertrophic cardiomyopathy. Also, it discusses the current evidence for the role of CMR in myocardial tissue characterization, as well as other imaging methods that have shown promise in FD. Current knowledge of the evaluation of the presence and extent of cardiac involvement at baseline and during follow-up of enzyme therapy efficiency are further presented. Multiple studies demonstrated that imaging parameters can be reliably used in establishing diagnosis and monitoring therapy in FD. Given the rarity of this disorder, we conclude that awareness should be raised about these imaging 'red flags' and likely patients sent for evaluation in expert centres.